2016
DOI: 10.1002/lt.24477
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate inferior vena cava in liver transplantation: A note of caution when left renal vein ligation is needed

Abstract: In the case of a hemodynamically significant splenorenal shunt (SRS; spontaneous [5%-12%] (1) or surgical), ligation of the left renal vein (LRV) at its root into the inferior vena cava (IVC) is indicated during liver transplantation (LT) in the following 2 situations:1. To improve the flow through portoportal anastomosis and prevent portal blood steal through the splenorenal siphon. (2,3) 2. To perform renoportal anastomosis in case of stage IV portal vein thrombosis. (4)(5)(6) In this setting, the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…2,3 As an example, one case report showed that a misdiagnosis of the left IVC as the left renal vein and subsequent inadvertent ligation of the left IVC led to deep vein thrombosis in the iliac and deep leg veins. 4 Preoperative identification is especially important for renal surgery, done by laparoscopic approaches, where a limited field of view can pose challenges for the identification of vascular anomalies. 2 IVC duplication is most often discovered incidentally upon radiologic investigation.…”
Section: Cuaj -Images In Urologymentioning
confidence: 99%
“…2,3 As an example, one case report showed that a misdiagnosis of the left IVC as the left renal vein and subsequent inadvertent ligation of the left IVC led to deep vein thrombosis in the iliac and deep leg veins. 4 Preoperative identification is especially important for renal surgery, done by laparoscopic approaches, where a limited field of view can pose challenges for the identification of vascular anomalies. 2 IVC duplication is most often discovered incidentally upon radiologic investigation.…”
Section: Cuaj -Images In Urologymentioning
confidence: 99%
“…Pode haver também outras variações, como VCI direita dupla ou VCI esquerda dupla, além de VCI dupla com continuação do hemiázigo da veia cava esquerda. 1,2,4,5 Essa condição, geralmente assintomática, pode gerar complicações na colocação do filtro de veia cava, e podendo também ser confundida com um linfonodo, tendo por isso, implicações clínicas. Além disso, pode estar associada a várias outras malformações, vasculares e não vasculares, havendo, também, um risco aumentado de eventos tromboembólicos.…”
Section: Duplicação De Veia Cava Inferiorunclassified
“…Nesse processo, podem ocorrer malformações anatômicas raras, usualmente assintomáticas, sendo um achado incidental em exames de imagem, principalmente através de Tomografia Computadorizada (TC), podendo ser erroneamente diagnosticadas como massas, levando a um tratamento incorreto. [1][2][3][4][5][6][7]…”
unclassified